The ORKA-HPC Compiler — Practical OpenMP for FPGAs - Mayer, Florian; Brandner, Julian; Hellmann, Matthias; Schwarzer, Jesko; Philippsen, Michael (Proceedings of the 34th International Workshop on Languages and Compilers for Parallel Computing (LCPC 2021), 2022)
ORKA-HPC is a new and downloadable OpenMP-to-FPGA compiler that is easy to set up, easy to use, and easy to extend. It targets a variety of different FPGA-boards, and is distributed with a “batteries included” runtime and development environment. Starting from a set of properties that such a compiler must possess, we derive how ORKA-HPC achieves these, reason about the underlying decisions, and evaluate ORKA-HPC’s current state of development. The paper concludes with future work and provides a download link.